2013
DOI: 10.1172/jci71349
|View full text |Cite
|
Sign up to set email alerts
|

CotH3 mediates fungal invasion of host cells during mucormycosis

Abstract: Angioinvasion is a hallmark of mucormycosis. Previously, we identified endothelial cell glucose-regulated protein 78 (GRP78) as a receptor for Mucorales that mediates host cell invasion. Here we determined that spore coat protein homologs (CotH) of Mucorales act as fungal ligands for GRP78. CotH proteins were widely present in Mucorales and absent from noninvasive pathogens. Heterologous expression of CotH3 and CotH2 in Saccharomyces cerevisiae conferred the ability to invade host cells via binding to GRP78. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
302
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(307 citation statements)
references
References 57 publications
3
302
0
2
Order By: Relevance
“…These results confirm our previous findings that adherence to and invasion of the endothelium are 2 independent processes mediated by different receptors (4,5). Additionally, BHB must upregulate the expression of receptors controlling adhesion of the fungus to the endothelium.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results confirm our previous findings that adherence to and invasion of the endothelium are 2 independent processes mediated by different receptors (4,5). Additionally, BHB must upregulate the expression of receptors controlling adhesion of the fungus to the endothelium.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, interactions of Mucorales with the endothelial cell lining of the blood vessels represent a critical step in the pathogenesis of mucormycosis. We have shown that Mucorales adhere to and invade endothelial cells (3) by expressing CotH proteins (4). CotH proteins bind to the heat shock host receptor glucose-regulated protein 78 (GRP78) (5), causing host cells to endocytose the organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed also the iron permease FTR1 and the surface protein cotH as known factors contributing to the virulence of these species. 23,53 However, both factors are present in a variety of mucoralean fungi and are not sufficient to explain the clinical importance of certain species. Comparative analyses of closely related virulent and non-virulent species may improve the understanding of the evolution of the pathogenicity mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of CotH in R. oryzae by siRNA or treatment with an anti-CotH antiserum inhibits the capacity of this organism to invade human umbilical vein endothelial cells in vitro. Similarly, shRNA knockdown of GRP78 in endothelial cells or treatment with an anti-GRP78 antiserum also significantly reduces fungal invasion of endothelial cells in vitro Gebremariam et al 2014).…”
Section: Mucoralesmentioning
confidence: 90%
“…In addition, several different Mucorales members bind to GRP78 in vitro. Finally, mice with diabetic ketoacidosis have increased mRNA levels of grp78 in the lungs and brain, providing a possible explanation for why the presence of diabetic ketoacidosis is a unique risk factor for mucormycosis in patients Gebremariam et al 2014). Therefore, it is likely that the induction of endocytosis via the interaction of CotH with GRP78 is a central mechanism by which Mucorales invade endothelial cells and perhaps other types of host cells.…”
Section: Mucoralesmentioning
confidence: 99%